2018
DOI: 10.1051/shsconf/20184902016
|View full text |Cite
|
Sign up to set email alerts
|

Principle of generator HHO hybrid multistack type production technologies to increase HHO gas volume

Abstract: Hydrogen isclassified as New Energy and also considered as the most promising transportation fuel candidate in the future. Various pilots test of hydrogen fuel cell vehicles by the world's leading automotive industries since the last 50 years have begun to show bright spot in the utilization of hydrogen-based fuel cells as vehicle fuel. The electrolysis process of water (H2O) would produce H2 (hydrogen) and O2 (oxygen). The conventional method resulted in inconsistent volume and quality of HHO gas. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…As the concentration of electrolytes increases, the conductivity of the solution also increases, which increases the current flow in the solution. This causes the solution to produce a larger current [10]. In addition, the concentration of the electrolytes also depends on the demand of the flow rate of brown gas.…”
Section: Effect Of Electrolyte On the Brown Gas Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the concentration of electrolytes increases, the conductivity of the solution also increases, which increases the current flow in the solution. This causes the solution to produce a larger current [10]. In addition, the concentration of the electrolytes also depends on the demand of the flow rate of brown gas.…”
Section: Effect Of Electrolyte On the Brown Gas Productionmentioning
confidence: 99%
“…The oxyhydrogen generator is a system that uses the electrolysis principle, which converts water into hydrogen and oxygen gas [10]. Based on their architecture, oxyhydrogen generators are classified as either wet cell or dry cell [11].…”
Section: Introductionmentioning
confidence: 99%
“…it is, thus increasing the production and operating costs of the system. The wet-type gas runs at a more stable production rate too (Sudrajat et al, 2018). Constant solution of 0.5-1% KOH was kept for the entire course of the experiment.…”
Section: Hho Electrolyzermentioning
confidence: 99%
“…The reviews by Essuman et al, [51] found that increasing the number of neutral plates between the cathode and anode will reduce the system potential. As the neutral plate between the anode and cathode increases, the potential between the stacks decreases [17]. As a result, the potential drop leads to increased temperature, which increases ion mobility, effectively collides, and causes a significant increase in HHO gas production [19].…”
Section: Effects Of Electrode Configuration On the Productionmentioning
confidence: 99%